Increased C reactive protein in response to acute stress in patients with rheumatoid arthritis. Issue 9 (11th February 2005) - Veldhuijzen van Zanten, J J C S; Ring, C; Carroll, D; Kitas, G D
Abstract : Objective: To assess the effects of acute stress on inflammatory, haemostatic, rheological, and haemodynamic activity in patients with rheumatoid arthritis (RA) in comparison with patients with osteoarthritis (OA). Methods: 21 patients with RA and 10 with OA underwent a brief mental stress task while standing. Inflammatory, haemostatic, rheological, and haemodynamic variables were measured at baseline, during the task, and at recovery. Results: At baseline, erythrocyte sedimentation rate and fibrinogen were higher in RA than OA. White blood cell count, fibrinogen, blood pressure, and pulse rate increased, whereas prothrombin time and plasma volume decreased during the task in both patient groups. The stress task increased C reactive protein (CRP) only in patients with RA, and more specifically in those patients with RA with high disease activity. Conclusions: The increase in the inflammatory marker CRP, which was specific to patients with RA, combined with the haemostatic, rheological, and haemodynamic reactions to the stress task, over and above the already high baseline levels, could underlie the increased risk for myocardial infarction in this vulnerable patient group.